Challenges of Analysing Gene-Environment Interactions in Mouse Models of Schizophrenia - Peter L. Oliver (The Scientific World Journal)
The modelling of neuropsychiatric disease using the mouse has provided a wealth of information regarding the relationship between specific genetic lesions and behavioural endophenotypes. However, it is becoming increasingly apparent that synergy between genetic and nongenetic factors is a key feature of these disorders that must also be taken into account. With the inherent limitations of retrospective human studies, experiments in mice have begun to tackle this complex association, combining well-established behavioural paradigms and quantitative neuropathology with a range of environmental insults. The conclusions from this work have been varied, due in part to a lack of standardised methodology, although most have illustrated that phenotypes related to disorders such as schizophrenia are consistently modified. Far fewer studies, however, have attempted to generate a “two-hit” model, whereby the consequences of a pathogenic mutation are analysed in combination with environmental manipulation such as prenatal stress. This significant, yet relatively new, approach is beginning to produce valuable new models of neuropsychiatric disease. Focussing on prenatal and perinatal stress models of schizophrenia, this review discusses the current progress in this field, and highlights important issues regarding the interpretation and comparative analysis of such complex behavioural data.